Determinants of quality of life improvements in anxiety and depressive disorders—A longitudinal study of inpatient psychotherapy - Freidl, Marion; Wegerer, Melanie; Litvan, Zsuzsa; König, Daniel; Alexandrowicz, Rainer W.; Portela-Millinger, Filipe; Gruber, Maria (Frontiers in Psychiatry, 2022)
Background: Quality of life (QoL) is substantially impaired in patients with anxiety disorders (AD) and depressive disorders (DD) and improvements in symptom burden after psychotherapy are not always paralleled by similar improvements in QoL. So far, little is known about treatment outcome in terms of QoL and predictors of QoL improvements following inpatient psychotherapy with a focus on cognitive behavior therapy (CBT). The current study aimed at investigating the relationship between changes in symptoms and QoL across different life domains. Additionally, predictors of a positive treatment outcome were evaluated. Methods: 122 patients with AD and/or DD undergoing an 8-weeks inpatient CBT program completed self-report measures of psychopathological symptoms and QoL at pre- and post-treatment. Mixed effects models were used to investigate changes, a confirmatory factor analysis was applied to analyze the latent factor structure of the anxiety sensitivity index and binary logistic regression analyses were performed for predictors of QoL improvements. Results: Patients showed moderate to strong decreases in anxious and depressive symptoms and moderate to strong improvements in general QoL, particularly in the psychological and physical QoL subdomains. Changes in symptom burden correlated most strongly with psychological and physical QoL. In addition, poor QoL before treatment and low levels of specific anxiety sensitivity symptoms (items 1 and 5) significantly predicted improvement in QoL. Conclusions: Patients with poor QoL who are not as inhibited to openly express their anxious feelings particularly benefit from inpatient psychotherapy (individual and group) to improve their QoL. In contrast, our research suggests that patients who are too anxious to openly express their nervousness should receive additional social skills training, more focused treatment to build sufficient self-confidence to better engage in the treatment program. Therefore we propose social skills training.